Notary's Responsibility for the Deed of Power of Attorney in Original if the Applicant Provides False Information - Ananta Prakarsa, Tegar; Sri Darmadi, Nanang (Jurnal Konstatering, 2026)
Notaries are required to keep minutes of the deed, however, in Article 16 paragraph (2) of the UUJN, this obligation is excluded if the Notary issues a deed of power of attorney in originali. The purpose of this study is to determine: 1) The Notary's responsibility if the person appearing provides false information in making a deed of power of attorney in originali. 2) Legal protection for the Notary if the person appearing provides false information in making a deed of power of attorney in originali. This type of research is normative legal research. Using the statute approach method. The type of data used is secondary data derived from primary, secondary, and tertiary legal materials and also uses primary data as complementary data to support this research. The data collection method uses literature studies. The analysis in this research uses qualitative analysis. The results of the study concluded: 1) The Notary is only responsible for the certainty of the date, that it is true that on the date, day, month and year as stated in the original power of attorney, it is true that the person appearing before the Notary to make the original power of attorney and regarding the validity of the signature in the original power of attorney, the Notary is not responsible for the contents of the original power of attorney made by or in his presence, the contents of the original power of attorney are entirely the responsibility of the person appearing, because the original power of attorney is made based on the wishes or desires of the person appearing. 2) If a Notary is summoned by an investigator in relation to an original power of attorney deed made before him, the Notary Honorary Council, which then forms an Examining Council, will summon and examine the Notary first and if the Honorary Council gives approval to the Notary to comply with the investigator's summons to be asked for information regarding an original power of attorney deed made by or before him, then the Notary can request assistance from the Notary Honorary Council, this is done to protect the Notary and maintain the dignity and honor of the Notary's position.